IMPLEMENTASI KEGIATAN EKSTRAKURIKULER SEBAGAI SARANA PENGEMBANGAN EMOSI POSITIF ANAK USIA SEKOLAH DI MADRASAH IBTIDAIYAH NEGERI 1 BANYUWANGI - Nur Fauziah, Nahdiah; Mufidatur Rizqiya Permana, Ainur Rofik; Mu`alimin, Lailatul Usriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of positive emotions in elementary school children is an important aspect in character building and learning success. Madrasah Ibtidaiyah Negeri (MIN) 1 Banyuwangi has various extracurricular activities such as scouting, karate, futsal, dancing, painting, and samroh, which not only develop talents but also serve as a means of fostering positive emotions in students. This study aims to describe the implementation of extracurricular activities at MIN 1 Banyuwangi and analyze their contribution to the development of positive emotions in elementary school children. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Informants consisted of 1 school principal, 6 supervising teachers, 12 active students, and 3 classroom teachers. Data analysis used the Miles, Huberman, and Saldaña model through the stages of reduction, presentation, and conclusion drawing, as well as validity testing with triangulation. The results show that extracurricular activities at MIN 1 Banyuwangi play a significant role in fostering discipline, responsibility, empathy, cooperation, self-confidence, and spiritual peace. Each activity has its own emotional value according to its field. It is concluded that extracurricular activities are an effective instrument for shaping students' emotional, social, and spiritual balance and an integral part of character education in madrasahs.